Preferences of Hospital Pharmacists for the Different Attributes of Intravitreal Treatments for Neovascular Age-Related Macular Degeneration and Diabetic Macular Edema in Spain: The SEEKING Study - José Luis Poveda; Pablo Arnáiz; Silvia López; Belén Muñoz; Anxo Fernández-Ferreiro (Pharmacy)
The process of evaluation and selection of drugs in Spain is currently changing, with hospital pharmacists (HPs) having a growing relevance. This cross-sectional observational study aimed to assess HPs’ preferences for different hypothetical intravitreal treatments for neovascular age-related macular degeneration (nAMD) and diabetic macular edema (DME). Best corrected visual acuity (BCVA), ocular adverse events (AE), annual drug cost, available presentation, and mechanisms of action (MoA) were the selected attributes. A conjoint analysis was used. Ninety-one HPs completed the study. The mean (SD) age was 39.2 (10.2) years, 60.4% were female, and the mean (SD) time of experience as HP was 12.6 (8.3) years. For nAMD treatments, BCVA (38.6%) and ocular AE (27.3%) were the most important attributes, while annual drug cost (16.3%), available presentation (11.1%), and MoA (6.7%) were not as important. For DME drugs, BCVA (44.6%) and ocular AE (25.5%) were the most significant factors; annual drug cost (17.9%), the drug’s available presentation (7.3%), and MoA (4.8%) were not considered to be as crucial. Preferences were comparable independent of HP experience. Effectiveness and safety were the most important attributes when choosing a drug. Comprehending the significant characteristics for HPs could potentially improve their collaborative function within multidisciplinary teams involved in intravitreal treatments.